EVALUATION AND CHARACTERIZATON OF SCENTED RICES FOR GRAIN QUALITY CHARACTERS - Singh, R.K.; Singh, OMKAR (Annals of Agricultural Research, 2014)
Twenty scented rice varieties along with a national cheak Pusa Basmati-1 were evaluated for various physico-chemical characters to their possible use as donors in rice quality improvement programmes as well as for consumption and export purposes. Varieties showed wide range of variation for aroma and chalkiness of endosperm indicating broad scope for improvement through selection. The highest kermel length was recorded in Khao Dowk Mali 105 (8.33 mm) followed by KCN 80152 (7.89 mm) and Hawa Kikwai (7.72 mm) which may be utilized as donors for developing long grains varieties. Overall five varieties, namely Khao Dawk Mail 105, Pakistani Basmati, Khao Hawn, Basmati Sathi and Basmati Champaran were identified superior among all of them as well as over Pusa Basmati-1 for most of the quality characters, which can be used as donors for quality improvement as well as for consumption and export purposes.